2011
DOI: 10.3109/03630269.2011.642489
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Genotype Frequency of β-Thalassemia and Sickle Cell Disease Carriers in Halkidiki, Northern Greece

Abstract: A decade of screening (years 2000 to 2010) for hemoglobinopathies in 3,931 patients was performed at the General Hospital of Poligiros, Halkidiki, Northern Greece. Among the patients examined, 10.8% heterozygotes for β-thalassemia (β-thal) were found, as well as 4.1% with sickle cell disease and 1.2% with double β-thal/Hb S [β6(A3)Glu→Val] heterozygosity. Iron deficiency was observed in 23.4%. The geographical distribution in the region revealed a substantial incidence of hemoglobinopathies even in mountaino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…A recent survey of β S and beta thalassaemia within the Chalkidhiki peninsular (Kalleas et al, 2012) provides more detail about the modern day pattern of beta globin variants in one of the Greek β S hotspots. It is striking that the distribution of β S is highly patchy within the peninsular (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of β S and beta thalassaemia within the Chalkidhiki peninsular (Kalleas et al, 2012) provides more detail about the modern day pattern of beta globin variants in one of the Greek β S hotspots. It is striking that the distribution of β S is highly patchy within the peninsular (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Its distribution is very uneven and frequencies as high as 15% have been reported in certain geographic areas (5). For example, in Halkidiki, of 3931 hospitalized patients screened for haemoglobinopathies, 10.8% were identified as heterozygotes for beta-thalassaemia (6). Equally, molecular analysis of 199 unrelated patients in south-western Greece confirmed distinct distribution patterns of specific mutations of the HBB gene in the Achaia and Ilia prefectures (7).…”
Section: Introductionmentioning
confidence: 95%
“…It is believed that codon 39 (C> T) is of Roman origin, and has a high prevalence in Sardinia, mainland Italy, Spain, Portugal and Tunisia (19). Different studies also found this mutation to be frequent in Venezuela (18), Northern Greece (20), Syria (21), and confirmed it in Tunisia (22) and Italy (23).…”
mentioning
confidence: 75%